The impact of stay-at-home orders on vulnerability assessments and precautionary intentions during a pandemic. Issue 5 (28th May 2023) - Rose, Jason P.; Edmonds, Keith A.; Aspiras, Olivia; Kumar, Megh; Scamaldo, Kayla; Richmond, Julia R.; Tull, Matthew T.; Gratz, Kim L.
ABSTRACT: In 2020, a novel emerging infectious disease – COVID-19 – became a global pandemic and prompted unprecedented social distancing measures. We examined the associations of voluntary stay-at-home (SAH) orders during the COVID-19 pandemic with vulnerability assessments and precautionary intentions (e.g. social distancing, hand washing). A quasi-experimental study using an online adult sample was conducted in U.S. states with and without voluntary SAH orders during the COVID-19 pandemic. Self-report surveys assessed vulnerability assessments and precautionary intentions. Participants living in states with SAH orders showed inflated vulnerability assessments for contracting COVID-19, and this association was stronger for affect-laden than cognitively-based assessments. Moreover, only affect-laden vulnerability assessments were uniquely associated with precautionary intentions and accounted for the relationship between SAH orders and precautionary intentions. Our study was among the first to explore the impact of voluntary SAH orders on vulnerability assessments and precautionary intentions. Results are discussed in terms of their implications for health behavioral models and applications for promoting self-protective actions during a pandemic.